2010
DOI: 10.1016/j.neuroscience.2009.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated expression of oncomodulin, the beta isoform of parvalbumin, in perikarya and axons in the diencephalon of parvalbumin knockout mice

Abstract: Abstract-The calcium-binding proteins parvalbumin, calbindin D-28k, calretinin and calcineurin are present in subsets of GABAergic gigantic calyciform presynaptic terminals of the reticular thalamic nucleus (RTN). Previously it was hypothesized that GABA and calcium-binding proteins including parvalbumin are not only colocalized in the same neuron subpopulation, but that GABA synthesis and parvalbumin expression could be also genetically regulated by a common mechanism. Moreover, parvalbumin expression levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…An extracellular role for OM in retinal ganglion cell regeneration (Yin et al 2006) was reported, but see also Hauk et al (2008) and Schwaller (2009). An up-regulation of OM occurs in PV 2/2 mice in a sparse subpopulation of neurons in the thalamus and in the dentate gyrus, as well as in partly varicose axons in the diencephalon (Csillik et al 2010). The functional significance of ectopic OM expression and the exact identity of neurons expressing OM in PV 2/2 mice remain to be shown.…”
Section: Functional Aspects Of Parvalbumin and Oncomodulinmentioning
confidence: 98%
“…An extracellular role for OM in retinal ganglion cell regeneration (Yin et al 2006) was reported, but see also Hauk et al (2008) and Schwaller (2009). An up-regulation of OM occurs in PV 2/2 mice in a sparse subpopulation of neurons in the thalamus and in the dentate gyrus, as well as in partly varicose axons in the diencephalon (Csillik et al 2010). The functional significance of ectopic OM expression and the exact identity of neurons expressing OM in PV 2/2 mice remain to be shown.…”
Section: Functional Aspects Of Parvalbumin and Oncomodulinmentioning
confidence: 98%
“… 9 Oncomodulin has only been detected in the nervous system of mice lacking α-parvalbumin expression [50]. …”
Section: Figmentioning
confidence: 99%
“…Although most neurons express a typifying cytosolic Ca 2+ buffer protein in the brain, CBPs can occasionally co-localize [32,48,49]. Nevertheless, neurons appear to commit to certain Ca 2+ buffers since genetic removal of a CBP is usually not compensated by up-regulation of expression of another EF-hand CBP superfamily member (see however, [50]).…”
Section: Introduction: Brief Overview Of Ca2+-binding Proteins Witmentioning
confidence: 99%
“…The PVs from both mammalian and fish skeletal muscle have relatively similar cation binding properties, especially with regard to possessing slow rates of Ca 2+ dissociation (White, 1988; Eberhard and Erne, 1994; Lee et al, 2000; Erickson and Moerland, 2006). On the other hand, mammalian β-PV, which is found in the brain, ear, placenta, and macrophages [not normally found in muscle (Belkacemi et al, 2002; Yin et al, 2006; Csillik et al, 2010)] has drastically lower affinity for both Ca 2+ and Mg 2+ compared to mammalian α-PV (Hapak et al, 1989). The rates of Ca 2+ and Mg 2+ exchange from mammalian β-PV are currently unknown and will be addressed in this manuscript.…”
Section: Introductionmentioning
confidence: 99%